2019
DOI: 10.1038/s41598-019-49481-7
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-tocopherol fertigation confers growth physio-biochemical and qualitative yield enhancement in field grown water deficit wheat (Triticum aestivum L.)

Abstract: Water stress is a major problem to fulfill the world food demand and to solve the problem of malnutrition. Different strategies are being used to solve these problems including the fertigation of plants with different biochemical at different growth stages. The present study was conducted for the induction of drought tolerance in field grown wheat for better yield and nutritional quality through foliar spray of α-tocopherol (α-Toc) at start of reproductive stage. Water stress was maintained based on number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 37 publications
3
49
0
1
Order By: Relevance
“…In the present study, the limited irrigation adversely affected growth and yield of sunflower plants. Previous studies revealed that the final production depends on the biomass status of the plants [8]. Similar is in the present findings where exogenous application of FeSO 4 and Fe-Asp, when applied foliary, significantly improved the plant growth and yield, being more improvement in sunflower plants foliary fertigated with Fe-Asp in comparison to FeSO 4 .…”
Section: Plant Growth and Seed Yieldsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, the limited irrigation adversely affected growth and yield of sunflower plants. Previous studies revealed that the final production depends on the biomass status of the plants [8]. Similar is in the present findings where exogenous application of FeSO 4 and Fe-Asp, when applied foliary, significantly improved the plant growth and yield, being more improvement in sunflower plants foliary fertigated with Fe-Asp in comparison to FeSO 4 .…”
Section: Plant Growth and Seed Yieldsupporting
confidence: 91%
“…The foliary-applied Fe sources improved the oxidative stress tolerance of sunflower plants when grown under limited water supply by increasing the activities of antioxidative enzymes such as APX, POD, SOD CAT, and the accumulation of non-enzymatic components such as TPC, TFC, AsA, and tocopherols. This improvement in the antioxidant components is due to the foliar application of FeSO 4 and Fe-Asp that correlate well with the lowered MDA and H 2 O 2 contents, showing less damage to cellular membranes [8,93,94].…”
Section: Improvement In Antioxidative Defense Mechanismmentioning
confidence: 52%
See 2 more Smart Citations
“…If the amount of antioxidants is reduced in response to stressful conditions, then the oxidative damages caused to the photosynthetic machinery result in ultimate cell death [10]. Among non-enzymatic components, carotenoids, ascorbic acid (AsA), and phenolics are considered as the most important ones among others due to their antioxidative and biological characteristics [11,12]. The contribution of ascorbic acid in the cellular antioxidative defense mechanism [7] has been described in the Halliwell-Asada pathway in detail.…”
Section: Introductionmentioning
confidence: 99%